Data Marketplaces: Trends and Monetisation of Data Goods - Markus Spiekermann (Intereconomics, 2019)
Despite the large number of academic contributions, there is no uniform definition of data marketplaces.However, different data marketplaces may vary from eachother in terms of their underlying business model, type ofdata offered, functionality, market mechanisms, etc.
Keywords: 330